2023
DOI: 10.1002/saj2.20553
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and microscale distribution of phosphorus compounds accumulated in continuously fertilized greenhouse soils

Abstract: The overuse of phosphate fertilizer results in the accumulation of surplus phosphorus (P) compounds in soil, and this trend is particularly intense in greenhouse farming.We aimed to characterize P compounds in greenhouse soils by comparing their speciation in soil samples collected from greenhouses and an open field. Two soil types with different phosphate sorption abilities, namely, Ultisol and Andisol, were considered. Phosphorus compounds in the soil were characterized by bulk soil analysis via acid extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…To determine the less soluble Ca‐P species in the soils, two acid extractions of the soils were performed: (1) 0.001 M H 2 SO 4 (pH = 3), which dissolves the readily available soil P (Truog‐P) (Truog, 1930), and (2) 0.44 M acetic acid (Ac‐P), which is a proximate total soil Ca‐P determination (Yamaguchi et al., 2023). The difference between the dissolved P from these two acid extractions is an estimate of less soluble soil Ca‐P (Yamaguchi et al., 2023). For the Truog‐P extraction, 0.15 g soil was added to 30 mL 0.001 M H 2 SO 4 (pH = 3 adjusted with ammonium sulfate) and shaken for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the less soluble Ca‐P species in the soils, two acid extractions of the soils were performed: (1) 0.001 M H 2 SO 4 (pH = 3), which dissolves the readily available soil P (Truog‐P) (Truog, 1930), and (2) 0.44 M acetic acid (Ac‐P), which is a proximate total soil Ca‐P determination (Yamaguchi et al., 2023). The difference between the dissolved P from these two acid extractions is an estimate of less soluble soil Ca‐P (Yamaguchi et al., 2023). For the Truog‐P extraction, 0.15 g soil was added to 30 mL 0.001 M H 2 SO 4 (pH = 3 adjusted with ammonium sulfate) and shaken for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, many sequential extraction tests have been developed to interpret speciation of P in the soils (Zhang & Kovar, 2009); however, their accuracy is often critiqued (Barrow et al, 2020). A recent study combined solid-phase nuclear magnetic resonance spectroscopy with P extractions of Andisol and Ultisol soils (pH 6.54-6.77) to discern P species targeted by 0.44 M acetic acid extraction (pH 2.56) and confirmed that the Ca-associated P peak in the soil disappeared after extraction, indicating the dissolution of the Ca-P minerals in the soils (Yamaguchi et al, 2023). They also showed that a soil extraction that used 0.001 M sulfuric acid solution at pH 3, called Truog-P, dissolved the readily soluble Ca-P but not the less soluble Ca-P that was extracted with the acetic acid extraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation